Determination of an optimal treatment margin for intracranial tumours treated with radiotherapy at Groote Schuur Hospital - Vos, Andre (Division of Radiology, 2021)
Background Accurate delivery of radiotherapy is a paramount component of providing safe oncological care. Margins are applied when planning radiotherapy to account for subclinical tumour spread, physiological movement and set-up error. Set-up error is unique to each radiotherapy institution and should be calculated for each organ site to ensure safe delivery of treatment. Aim and setting The aim of this study is to calculate the random and systematic set-up error for a cohort of patients with intracranial tumours treated with 3D Conformal Radiotherapy at the Department of Radiation Oncology, Groote Schuur Hospital, South Africa. After obtaining above mentioned data the ideal CTV-PTV expansion margin was calculated using published CTV-PTV expansion margin recipes. Patients and methods The Electronic Portal Images (EPID) of 20 patients who met the inclusion criteria were compared to their Digitally Reconstructed Radiograph (DRR). The set-up error for each patient was measured after which the random (s) and systematic (S) set-up error for the study group could be calculated. With both these values known the CTV-PTV expansion margin could be determined. Results The largest error was in the Superior/Inferior (SI) direction, followed by the Medial/Lateral (ML) direction and least in the Anterior/Posterior (AP) direction with 87.7%, 76.2% and 91.6% of the errors in the ML, SI and AP directions respectively being less than 3mm. There was no error larger than 5mm in the ML or AP direction with 6.1% of the SI error larger than 5mm. The random and systematic error in all three directions for this patient cohort were less than 2mm conforming to acceptable standards of delivering safe radiotherapy. Using Stroom's margin recipe (2S + 0.7s) a CTV-PTV expansion margin of 5mm can safely be applied for this patient cohort. Conclusion When treating patients with intracranial tumours at Groote Schuur Hospital the CTV-PTV expansion margin can safely be reduced from 1cm to 5mm.